Teachers’ Interaction Strategy to Encourage Students’ Willingness to Communicate - Musrina, Musrina (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2018)
Being able to communicate using target language highly depends on the Willingness to Communicate (WTC). This study is aimed to find out what the difficulties encountered by the teacher when trying to encourage student?s WTC and how they cope the problems. This study took place in Ende East Nusa Tenggara. In collecting the data, the writer used semi-structure interview. The result revealed that there are some difficulties faced by the teacher while encouraging student?s WTC. Those were: the students were afraid of being corrected, incomprehensible input of the student related to the material and the learning schedule arrangement. The second, the teacher used teacher-fronted strategy that is also known as IRF, facilitator-oriented strategy and learner-oriented strategy to encourage student?s WTC. In conclusion, based on teachers? perspective, the students were willing to communicate if the teacher facilitated them by some suitable strategies. This study suggests any English teacher that should concern on WTC of student. The teacher should depend on good teaching: employing one strategy alone does not potentially bring success in encouraging student?s WTC. Then, employing all the three strategies in single meeting are possible to strongly encourage student?s willingness to communicate. Beyond that, this present study is expected to contribute to the comprehension of